PENGARUH PERCEIVED RISK, PERCEIVED WAITING TIME, PERCEIVED INCONVENIENCE TRANSACTION TERHADAP ABANDON SHOPPING CART DI TOKOPEDIA - Untung Prasetya Purwoko; Siti Rahayu; Veny Megawati (CALYPTRA, 2018)
This study aims to determine the effect of Perceived risk, Per Waitning Time, Perceived Inconvenience Transaction to Abandon Shopping Cart. The object used is Tokopedia, as it is the largest original Indonesian online store. The results of this study show that Perceived risk has no positive effect on Abandon shoping cart, Positive Time Waiting Feelings of Abandon shoping cart, Perceived Inconvenience Transaction Positive to Abandon shoping cart.